To convert the equation \(0.4x + 0.2y = 0.6\) into slope-intercept form, which is \(y = mx + b\) (where \(m\) is the slope and \(b\) is the y-intercept), follow these steps:
-
Isolate \(y\). Start by moving the term with \(x\) to the other side:
\[ 0.2y = -0.4x + 0.6 \]
-
Divide every term by the coefficient of \(y\) (which is 0.2) to solve for \(y\):
\[ y = \frac{-0.4}{0.2}x + \frac{0.6}{0.2} \]
-
Simplify the fractions:
\[ y = -2x + 3 \]
So, the slope-intercept form of the equation \(0.4x + 0.2y = 0.6\) is:
\[ y = -2x + 3 \]